The nonlinear effect of time pressure on innovation performance: New insights from a meta-analysis and an empirical study - Song, Haojie; Gao, Renjing; Zhang, Qiang; Li, Yongxin (Frontiers in Psychology, 2023)
As competition grows, when employees are required to accelerate innovation, they also face increasing time pressure. In order to shed light on how time pressure affects employees’ innovation performance, two studies were conducted to examine the effect of time pressure on innovation performance. In Study 1, based on 50 effect sizes from 50 independent samples (N = 15,751) in 40 articles, a meta-analysis was conducted to examine the J-shaped effect of time pressure on innovation performance. In Study 2, based on a two-wave survey of 645 employees, the mechanism underlying the J-shaped effect of time pressure on innovation performance was explored. Results from Study 1 revealed that time pressure had a J-shaped effect on innovation performance, such that high levels of time pressure had a more positive effect on innovation performance. Results from Study 2 showed that learning behavior significantly mediated the J-shaped effect of time pressure on innovation performance, and that supervisor developmental feedback moderated the intermediary process. These results deepen the understanding of the relationship between time pressure and innovation performance, and provide practical advice on how to manage innovation performance under time pressure.